THE EFFECTIVENESS OF LIPASE IMMOBILIZATION ON CHITOSAN BEADS CROSS-LINKED BY GLUTARALDEHYDE - Lizma Febrina (PROSIDING SEMINAR KIMIA, 2015)
The effectiveness of immobilized lipase on chitosan bead with glutaraldehyde as cross-linker compounds has been carried out. This research aims to obtain optimal condition for immobilization of lipase on chitosan bead. Chitosan bead made from chitosan powder by inverse phase method. This research started from the optimization process of immobilization for the optimum concentration of glutaraldehyde as cross-linker compounds. Immobilized lipase on chitosan beads was tested for its activities and stability of re-uses in the hydrolysis reaction of palm oil triglycerides. The optimum concentration of glutaraldehyde is 0,5% (v/v) with immobilization enzyme percentage 84% and specific activities of immobilized of lipase 82 U/g. Immobilized lipase has lower activities than free lipase. But it have the relative activity of 70% after 5 times of use, while the free lipase enzymes 4% after 5 times of use. This indicates the stability of the re-use of lipase immobilized better than free lipase.